2016
DOI: 10.1021/acs.est.6b01010
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination in Degradability of Soil Pyrogenic Organic Matter Follows a Return-On-Energy-Investment Principle

Abstract: A fundamental understanding of biodegradability is central to elucidating the role(s) of pyrogenic organic matter (PyOM) in biogeochemical cycles. Since microbial community and ecosystem dynamics are driven by net energy flows, then a quantitative assessment of energy value versus energy requirement for oxidation of PyOM should yield important insights into their biodegradability. We used bomb calorimetry, stepwise isothermal thermogravimetric analysis (isoTGA), and 5-year in situ bidegradation data to develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 24 publications
4
26
0
Order By: Relevance
“…All biochars in this study were found to have an "intermediate" C sequestration potential (Class B), between that of soot/graphite and uncharred plant biomass, regardless of weathering extent. These R 50 values combined with relatively low ROI values [compared to those studied by Harvey et al (2016)] indicate that the microbial decomposition of the biochars in this study would be dominated by co-metabolism. Co-metabolism is the simultaneous degradation of two substrates, in which the degradation of the secondary substrate, in this case the biochar, depends on the presence of a primary substrate (glucose, dissolved organic matter, etc.…”
Section: Variation In Biochar Recalcitrance With Weatheringmentioning
confidence: 67%
See 3 more Smart Citations
“…All biochars in this study were found to have an "intermediate" C sequestration potential (Class B), between that of soot/graphite and uncharred plant biomass, regardless of weathering extent. These R 50 values combined with relatively low ROI values [compared to those studied by Harvey et al (2016)] indicate that the microbial decomposition of the biochars in this study would be dominated by co-metabolism. Co-metabolism is the simultaneous degradation of two substrates, in which the degradation of the secondary substrate, in this case the biochar, depends on the presence of a primary substrate (glucose, dissolved organic matter, etc.…”
Section: Variation In Biochar Recalcitrance With Weatheringmentioning
confidence: 67%
“…), and is also known as the priming effect (Luo et al 2011;Zimmerman and Ouyang 2019). The ROI values associated with our biochar suggests relatively low biodegradability on "short to medium time scales" according to Harvey et al (2016). Assuming steady-state average losses of 0.9-1.2% biochar C year −1 suggests a relatively high turnover rate and low biochar residence time of 83-111 years for the pyrolysis temperature and feedstock (450 °C, mixed hardwood).…”
Section: Variation In Biochar Recalcitrance With Weatheringmentioning
confidence: 85%
See 2 more Smart Citations
“…Furthermore, Williams and Plante propose a bioenergetics framework for assessing the persistence of organic matter in soil systems. The framework is based on a return-on-investment ratio, the ratio between energy invested in relation to energy density (Harvey et al, 2016). Their framework contradicts traditional humus theory that organic matter is composed of inherently stable macromolecules; instead it supports the idea that organic matter is a continuum of progressively decomposing organic compounds (Lehmann and Kleber, 2015).…”
Section: Soil Biogeochemistrymentioning
confidence: 98%